Diagnostic Accuracy of Peritoneoscopy to Determine the Cause of Low Serum Ascites Albumin Gradient - Parajuli, Pawan; Bhandari, Ramesh S; Pathak, Rahul; Sharma, Shashi; Khadga, Prem K; Jha, Anurag; Hamal, Rabin; Kafle, Brindeswari (Journal of Institute of Medicine Nepal, 2019)
Introduction: As cites, a common entity in practice of gastroenterology is path physiologically divided into high SAAG and low SAAG category, to rapidly classify, formulate a workup plan and expedite the diagnosis. The cause of low SAAG as cites is often due to local peritoneal cause e.g. peritoneal tuberculosis, peritoneal carcinomatosis etc, mandating the need of peritoneoscopy for definitive diagnosis. This study aims to present the peritoneoscopy and peritoneal biopsy result of patients with low SAAG as cites of uncertain etiology.Methods: Peritoneoscopy was prospectively performed in 12 patients with low SAAG as cites of unclear etiology. Patients with low SAAG as cites and willing to give consent for peritoneoscopy were enrolled in the study. Patients underwent laparoscopic peritoneoscopy under general anesthesia and appropriate biopsies were taken during the procedure for histopathological analysis.Results: Of the twelve patients with low SAAG enrolled in the study, 3 (25%) were male and 75% (9) were female. The success rate of the procedure was 100% and there was no procedure related complications. Specific findings were seen in all patients undergoing peritoneoscopy. Of the twelve patients, 9 (75%) patients has metastatic deposits in the peritoneum, 3 (25%) had benign etiology, 2/3rd (2) of whom had granulomatous deposits suggestive of tuberculosis and 1/3rd (1) had extensive dense adhesions and peritoneal fibrosis. Primary focus was revealed (ovary) in only 1 patient undergoing peritoneoscopy.Conclusion: Peritoneoscopy with simultaneous biopsy is safe, efficient and accurate diagnostic method due to its high diagnostic capacity and low complication rate in selected patients who have low SAAG as cites of uncertain etiology.